Determinants of Peer Support on the Potential for Drug Abuse Among Adolescents - syarniah, syarniah; Firdaus, Syamsul; Rachmadi, Agus (Poltekkes Kemenkes Banjarmasin, 2025)
Drug abuse among adolescents is a serious problem that has widespread negative impacts, including on physical and mental health, social relationships, and academic achievement. Factors contributing to drug abuse among adolescents include internal factors and environmental factors. An environment that has the potential to make it easy to fall prey to the influence of peers or family environment. The objective is to analyze the determinants of peer influence on the risk of drug abuse among adolescents. The population of high school and Islamic high school students, with a sample of 1,184 students from the population of high school and Islamic high school students in South Kalimantan. Modified instruments sourced from the National Narcotics Agency were collected using Google Forms through school principals and distributed simultaneously. The data was analyzed using Spearman's rho test. The Spearman Correlation Test results show that there is a relationship between the peer factor variable and the drug abuse variable, with a correlation coefficient of rs = -0.107 and a significance level of p=0.000; α. The solution from this research finding needs to strengthen positive peer groups that are close to religious youth groups or close to sports and arts clubs.